Immunosuppression in Dogs During Mammary Cancer Development. (November 2016) - Mucha, J.; Rybicka, A.; Dolka, I.; Szymańska, J.; Manuali, E.; Parzeniecka-Jaworska, M.; Kluciński, W.; Król, M.
Cancer immunosuppression that facilitates tumor progression and metastasis evolves by development of an immunosuppressive network. The aim of this study was to assess this network in dogs with benign or malignant tumors with or without confirmed metastasis. The authors showed that the number of various T cell subpopulations was constant during tumor development; however the number of regulatory T cells (Tregs) was significantly higher in tumor-bearing dogs than in healthy individuals. The number of myeloid-derived suppressor cells (MDSCs) and their p-STAT3 expression (which is a negative regulator of hematopoiesis and regulates VEGF expression) were higher in cancer patients than in control dogs, however their number increased significantly in late-stage cancer patients. Canine mammary carcinomas with confirmed metastases to either lymph nodes or internal organs had greater MDSCs and Treg infiltration than benign mammary tumors or malignant mammary tumors for which metastases had not been detected. Similarly, expression of p-STAT3 and VEGF-C was the highest in tumors with confirmed metastases. This research shows changes occurring in the blood (n = 30 patients) and tumor tissue of patients (n = 100) during canine mammary tumor development. The findings should be considered preliminary because of the small number of samples. Nonetheless, the findings suggest that a high level of Tregs and MDSCs as well as high expression of p-STAT3 and VEGF-C may significantly contribute to mammary tumor progression and metastasis in dogs.